Integrated analysis of field work, applied to the middle and lower basin of the Chillón river, Lima - Cabrera, Carlos (2001)
This research work is the result of field work carried out in the middle and lower basin of the Chillón river, during which a study of the main environmental variables was made, applying main field techniques. An environmental perception of the study area was carried out, photographs were recorded and water samples were analyzed in 04 hydrographic stations of the Chillón river, which led us to determine the quality of the water from the physical, chemical and microbiological point of view. It should be noted that the results found are related to the period of avenues characteristic of a rainy period prior to the El Niño event 1998-1999.